Proceedings of the Audio Mostly 2018 on Sound in Immersion and Emotion 2018
DOI: 10.1145/3243274.3243277
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Emotion of Isolated Synthetic Audio

Abstract: The ability of sound to enhance human wellbeing has been known since ancient civilisations, and methods can be found today across domains of health and within a variety of cultures. There are an abundance of sound-based methods which show benefits for both physical and mental-states of wellbeing. Current methods vary from low frequency vibrations to high frequency distractions, and from drone-like sustain to rhythmical pulsing, with limited knowledge of a listeners psycho-physical perception of this. In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…In this contribution, we made preliminary user studies on the effect of augmenting natural soundscapes, as well as proposing a 'next-step' methodology for a personalised version of such a system. A series of perception studies [39] including those by the authors [5], support the initial assumption that specific combinations of audio can alter states of individual wellbeing -and initial results in this contribution also show similar trends. Thus, these findings support further development of the work described herein.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In this contribution, we made preliminary user studies on the effect of augmenting natural soundscapes, as well as proposing a 'next-step' methodology for a personalised version of such a system. A series of perception studies [39] including those by the authors [5], support the initial assumption that specific combinations of audio can alter states of individual wellbeing -and initial results in this contribution also show similar trends. Thus, these findings support further development of the work described herein.…”
Section: Discussionsupporting
confidence: 62%
“…For the offline generation, perhaps in the scenario where a listener aims to reduce their affective state for short-term period, a pre-existing synthetic emotional source could be used. In this case, a dataset of synthetic audio could be applied, such as the richly annotated EmoSynth database [5]. From this, one-minute emotional samples can be created based on their emotional values; typically, this equates to aspects in audio such as, high arousal being equal to higher pitch and low arousal being equal lower pitch, with valence being a somewhat more complex aspect of emotion in terms of acoustic representation.…”
Section: Offline Audio Generationmentioning
confidence: 99%
“…Thus, considering that many studies evaluate only one of them, a synopsis of the state-of-the-art is hardly doable. Moreover, previous research on this topic is biased toward the study of classical music (Iwanaga & Moroki, 1999;Pelletier, 2004;Rohner & Miller, 1980), while less conventional genres and soundscapes (Truax, 2008) have rarely been considered (Baird, Parada-Cabaleiro, Fraser, Hantke, & Schuller, 2018;Thoma et al, 2013). Factors such as familiarity and preference have also been investigated: while some studies showed that listeners' relaxation is mostly elicited when the music is familiar (Mok &Wong, 2003) and likable (Jiang et al, 2013), others showed that music influences listeners' relaxation regardless of their preferences (Iwanaga & Moroki, 1999).…”
Section: Related Researchmentioning
confidence: 99%
“…Hence, given that participants were exposed to the two sounds (i.e., triangle wave and square wave) in the same experimental session, it is possible that participants judged the square wave sound as mbitter relative to the triangle wave sound. This association may be due to the different waveforms used (Knöferle & Spence, 2012), which at the same time may cause discrepancies in their perceived pitch (Hermes, 2023) and in their evoked valence (Baird, Parada‐Cabaleiro, Fraser, Hantke, & Schuller, 2018). In addition, previous research has found that specific timbres, in the form of musical notes produced by different musical instruments, can give rise to different taste associations (Crisinel & Spence, 2010b).…”
Section: Discussionmentioning
confidence: 99%